Impact of Microfinance on the Empowerment of Women Entrepreneurs in Rupandehi District, Nepal - Thapa, Bharat Singh; Chowdhary, Supriya (Journal of Business and Management, 2022)
Background: Driven by the growing concerns about women empowerment and their entrepreneurship development, government has put in place various microfinance programmes and policies providing increased access to financial services, mainly credit facilities. Objectives: This paper aims at evaluating the effect of microfinance programs on women entrepreneurs’ performance with respect to their economic and social empowerment. Methods: A structured questionnaire survey was made among 124 randomly selected women entrepreneurs taking loan from different microfinance institutions under group lending approach in Rupandehi district. Rupandehi district is known for pioneering in providing microfinance services in Nepal as first microfinance institution was established here about three decades ago. One sample t-test, Paired Sample t-test, Wilcoxon test and McNemar test are major statistical tools used for data analysis. Results: Results show that microfinance leads to increase in business turnover, investment, savings, expenditures and ownership in assets. Similarly, social dimensions of women entrepreneurs were also found improved after participation in microfinance programs. They include women’s freedom to decide, family and social relationship, mobility, children’s education and health. Conclusion: These findings revealed that microfinance is a powerful instrument to develop women entrepreneurship through economic and social empowerment. Thus, to foster the inclusive growth with the participation of women in economy, scale and scope of microfinance should be enhanced.